EFFECTS OF BA AND CPPU ON POLYAMINE CONTENT, SETTING AND DEVELOPMENT OF SEEDLESS GRAPES INDUCED BY GIBBERELLIN A3 - S. Shiozaki; R. Sakurai; M. Hotta; T. Ogata (Journal of Animal and Plant Sciences, 2014)
The effects of N6-benzyladenine (BA) and N-(2-chloro-4-pyridyl)-N¢-phenylurea (CPPU) in combination with gibberellic acid (GA3, 100 mg l–1) on berry setting and development and on the endogenous level of polyamines (PAs ) were investigated in order to elucidate the role of PAs in the setting and development of GA3-induced seedless grape berries affected by cytokinins. BA stimulated berry development, but not berry setting, while CPPU significantly stimulated berry setting. The PA synthesis inhibitors DL-a-difluoromethyl-arginine and methylglyoxal-bis(guanyl-hydrazone) inhibited the berry development induced by GA3 + BA at 11 days after full bloom. However, they did not inhibit the increased berry-setting rate induced by GA3 + CPPU. Application of BA in combination with GA3 greatly increased the levels of free putrescine and spermidine. CPPU had almost no effect on the levels of free PAs, but significantly increased conjugated PAs. The effect of the addition of BA and CPPU on levels of bound PAs was small compared with the effect on free and conjugated PAs.
Keywords: Berry set; Berry development; Cytokinin; Gibberellin; Polyamine; Seedless